The impact of the image conversion factor and image centration on retinal vessel geometric characteristics - Schanner, Carolin; Hautala, Nina; Rauscher, Franziska G.; Falck, Aura (Frontiers in Medicine, 2023)
Background This study aims to use fundus image material from a long-term retinopathy follow-up study to identify problems created by changing imaging modalities or imaging settings (e.g. image centering, resolution, viewing angle, illumination wavelength). Investigating the relationship of image conversion factor and imaging centering on retinal vessel geometric characteristics (RVGC), offers solutions for longitudinal retinal vessel analysis for data obtained in clinical routine. Methods RVGCs were analyzed in scanned fundus photographs with Singapore-I-Vessel-Assessment using a constant image conversion factor (ICF) and an individual ICF, applying them to macula centered (MC) and ODC) images. The ICF is used to convert pixel measurements into µm for vessel diameter measurements and to establish the size of the measuring zone. Calculating a constant ICF, the width of all analyzed optic disks is included, and it is used for all images of a cohort. An individual ICF, in turn, uses the optic disk diameter of the eye analyzed. To investigate agreement, Bland-Altman mean difference was calculated between ODC images analyzed with individual and constant ICF and between MC and ODC images. Results With constant ICF (n = 104 eyes of 52 patients) the mean central retinal equivalent was 160.9±17.08µm for arteries (CRAE) and 208.7±14.7.4µm for veins (CRVE). The individual ICFs resulted in a mean CRAE of 163.3±15.6µm and a mean CRVE of 219.0±22.3µm. On Bland-Altman analysis, the individual ICF RVGC are more positive, resulting in a positive mean difference for most investigated parameters. Arteriovenous ratio (p=0.86), simple tortuosity (p=0.08) and fractal dimension (p=0.80) agreed well between MC and ODC images, while the vessel diameters were significantly smaller in MC images (p<0.002). Conclusion Scanned images can be analyzed using vessel assessment software. Investigations of individual ICF versus constant ICF point out the asset of utilizing an individual ICF. Image settings (ODC vs. MC) were shown to have good agreement.